That would be D) The slope of the graph will be changed.
I hope it helps
Sound or vibration wave that is conducted
4x+8 = 32, 4x = 24, x = 6
I'll assume the ODE is actually
![y''+(x-2)y'+y=0](https://tex.z-dn.net/?f=y%27%27%2B%28x-2%29y%27%2By%3D0)
Look for a series solution centered at
, with
![y=\displaystyle\sum_{n\ge0}c_n(x-2)^n](https://tex.z-dn.net/?f=y%3D%5Cdisplaystyle%5Csum_%7Bn%5Cge0%7Dc_n%28x-2%29%5En)
![\implies y'=\displaystyle\sum_{n\ge0}(n+1)c_{n+1}(x-2)^n](https://tex.z-dn.net/?f=%5Cimplies%20y%27%3D%5Cdisplaystyle%5Csum_%7Bn%5Cge0%7D%28n%2B1%29c_%7Bn%2B1%7D%28x-2%29%5En)
![\implies y''=\displaystyle\sum_{n\ge0}(n+2)(n+1)c_{n+2}(x-2)^n](https://tex.z-dn.net/?f=%5Cimplies%20y%27%27%3D%5Cdisplaystyle%5Csum_%7Bn%5Cge0%7D%28n%2B2%29%28n%2B1%29c_%7Bn%2B2%7D%28x-2%29%5En)
with
and
.
Substituting the series into the ODE gives
![\displaystyle\sum_{n\ge0}(n+2)(n+1)c_{n+2}(x-2)^n+\sum_{n\ge0}(n+1)c_{n+1}(x-2)^{n+1}+\sum_{n\ge0}c_n(x-2)^n=0](https://tex.z-dn.net/?f=%5Cdisplaystyle%5Csum_%7Bn%5Cge0%7D%28n%2B2%29%28n%2B1%29c_%7Bn%2B2%7D%28x-2%29%5En%2B%5Csum_%7Bn%5Cge0%7D%28n%2B1%29c_%7Bn%2B1%7D%28x-2%29%5E%7Bn%2B1%7D%2B%5Csum_%7Bn%5Cge0%7Dc_n%28x-2%29%5En%3D0)
![\displaystyle\sum_{n\ge0}(n+2)(n+1)c_{n+2}(x-2)^n+\sum_{n\ge1}nc_n(x-2)^n+\sum_{n\ge0}c_n(x-2)^n=0](https://tex.z-dn.net/?f=%5Cdisplaystyle%5Csum_%7Bn%5Cge0%7D%28n%2B2%29%28n%2B1%29c_%7Bn%2B2%7D%28x-2%29%5En%2B%5Csum_%7Bn%5Cge1%7Dnc_n%28x-2%29%5En%2B%5Csum_%7Bn%5Cge0%7Dc_n%28x-2%29%5En%3D0)
![\displaystyle2c_2+c_0+\sum_{n\ge1}(n+2)(n+1)c_{n+2}(x-2)^n+\sum_{n\ge1}nc_n(x-2)^n+\sum_{n\ge1}c_n(x-2)^n=0](https://tex.z-dn.net/?f=%5Cdisplaystyle2c_2%2Bc_0%2B%5Csum_%7Bn%5Cge1%7D%28n%2B2%29%28n%2B1%29c_%7Bn%2B2%7D%28x-2%29%5En%2B%5Csum_%7Bn%5Cge1%7Dnc_n%28x-2%29%5En%2B%5Csum_%7Bn%5Cge1%7Dc_n%28x-2%29%5En%3D0)
![\displaystyle2c_2+c_0+\sum_{n\ge1}\bigg((n+2)(n+1)c_{n+2}+(n+1)c_n\bigg)(x-2)^n=0](https://tex.z-dn.net/?f=%5Cdisplaystyle2c_2%2Bc_0%2B%5Csum_%7Bn%5Cge1%7D%5Cbigg%28%28n%2B2%29%28n%2B1%29c_%7Bn%2B2%7D%2B%28n%2B1%29c_n%5Cbigg%29%28x-2%29%5En%3D0)
![\implies\begin{cases}c_0=2\\c_1=0\\(n+2)c_{n+2}+c_n=0&\text{for }n>0\end{cases}](https://tex.z-dn.net/?f=%5Cimplies%5Cbegin%7Bcases%7Dc_0%3D2%5C%5Cc_1%3D0%5C%5C%28n%2B2%29c_%7Bn%2B2%7D%2Bc_n%3D0%26%5Ctext%7Bfor%20%7Dn%3E0%5Cend%7Bcases%7D)
- If
for integers
, then
![k=0\implies n=0\implies c_0=c_0](https://tex.z-dn.net/?f=k%3D0%5Cimplies%20n%3D0%5Cimplies%20c_0%3Dc_0)
![k=1\implies n=2\implies c_2=-\dfrac{c_0}2=(-1)^1\dfrac{c_0}{2^1(1)}](https://tex.z-dn.net/?f=k%3D1%5Cimplies%20n%3D2%5Cimplies%20c_2%3D-%5Cdfrac%7Bc_0%7D2%3D%28-1%29%5E1%5Cdfrac%7Bc_0%7D%7B2%5E1%281%29%7D)
![k=2\implies n=4\implies c_4=-\dfrac{c_2}4=(-1)^2\dfrac{c_0}{2^2(2\cdot1)}](https://tex.z-dn.net/?f=k%3D2%5Cimplies%20n%3D4%5Cimplies%20c_4%3D-%5Cdfrac%7Bc_2%7D4%3D%28-1%29%5E2%5Cdfrac%7Bc_0%7D%7B2%5E2%282%5Ccdot1%29%7D)
![k=3\implies n=6\implies c_6=-\dfrac{c_4}6=(-1)^3\dfrac{c_0}{2^3(3\cdot2\cdot1)}](https://tex.z-dn.net/?f=k%3D3%5Cimplies%20n%3D6%5Cimplies%20c_6%3D-%5Cdfrac%7Bc_4%7D6%3D%28-1%29%5E3%5Cdfrac%7Bc_0%7D%7B2%5E3%283%5Ccdot2%5Ccdot1%29%7D)
and so on, with
![c_{2k}=(-1)^k\dfrac{c_0}{2^kk!}](https://tex.z-dn.net/?f=c_%7B2k%7D%3D%28-1%29%5Ek%5Cdfrac%7Bc_0%7D%7B2%5Ekk%21%7D)
- If
, we have
for all
because
causes every odd-indexed coefficient to vanish.
So we have
![y(x)=\displaystyle\sum_{k\ge0}c_{2k}(x-2)^{2k}=\sum_{k\ge0}(-1)^k\frac{(x-2)^{2k}}{2^{k-1}k!}](https://tex.z-dn.net/?f=y%28x%29%3D%5Cdisplaystyle%5Csum_%7Bk%5Cge0%7Dc_%7B2k%7D%28x-2%29%5E%7B2k%7D%3D%5Csum_%7Bk%5Cge0%7D%28-1%29%5Ek%5Cfrac%7B%28x-2%29%5E%7B2k%7D%7D%7B2%5E%7Bk-1%7Dk%21%7D)
Recall that
![e^x=\displaystyle\sum_{n\ge0}\frac{x^k}{k!}](https://tex.z-dn.net/?f=e%5Ex%3D%5Cdisplaystyle%5Csum_%7Bn%5Cge0%7D%5Cfrac%7Bx%5Ek%7D%7Bk%21%7D)
The solution we found can then be written as
![y(x)=\displaystyle2\sum_{k\ge0}\frac1{k!}\left(-\frac{(x-2)^2}2\right)^k](https://tex.z-dn.net/?f=y%28x%29%3D%5Cdisplaystyle2%5Csum_%7Bk%5Cge0%7D%5Cfrac1%7Bk%21%7D%5Cleft%28-%5Cfrac%7B%28x-2%29%5E2%7D2%5Cright%29%5Ek)
![\implies\boxed{y(x)=2e^{-(x-2)^2/2}}](https://tex.z-dn.net/?f=%5Cimplies%5Cboxed%7By%28x%29%3D2e%5E%7B-%28x-2%29%5E2%2F2%7D%7D)